An Integrative Preventive-Curative Model for Child Victims of Domestic Violence in Ambon City from an Islamic Family Law Perspective - Rizal Darwis; Zumiyati Sanu Ibrahim; Lahaji; Andiani Rezkita Nabu; La Jamaa; Syarifuddin; A. Zamakhsyari Baharuddin (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2026)
Domestic violence causes multidimensional harm to children, yet existing responses remain partial, failing to integrate legal, psychological, spiritual, and local values. The qualitative case study in Ambon City, Indonesia, aimed to formulate an integrative preventive-curative model for child victims of domestic violence grounded in Islamic family law, Indonesian positive law, and maqāṣid al-syarī‘ah. Data were collected through semi-structured interviews with 20 informants (children, mothers, educators, psychologists, religious leaders, traditional leaders, and government officials) and a literature review. Then, the data analyzed using the Miles & Huberman model with a normative-Islamic legal approach, resulting in rechtvinding. Findings revealed a chronic trauma in children, including emotional disorders, educational neglect, post-traumatic stress disorder (PTSD), and depression. As its main scientific contribution, the particular study proposed a novel integrative preventive-curative model that synergizes Islamic family law, national legal instruments, and local institutional wisdom (saudara kawin) to achieve holistic child protection (maṣlaḥah al-ṭifl). The study concluded that tripartite synergy is essential for culturally grounded, replicable interventions for domestic violence-affected children in Muslim-majority contexts.